2023
DOI: 10.1007/s00520-023-07625-6
|View full text |Cite
|
Sign up to set email alerts
|

Blended online learning for oncologists to improve skills in shared decision making about palliative chemotherapy: a pre-posttest evaluation

Abstract: Purpose To improve shared decision making (SDM) with advanced cancer patients, communication skills training for oncologists is needed. The purpose was to examine the effects of a blended online learning (i.e. e-learning and online training session) for oncologists about SDM in palliative oncological care and to compare this blended format with a more extensive, fully in-person face-to-face training format. Methods A one-group pre-posttest design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This innovative, experimental study demonstrated that cancer patients and survivors (i.e., APs) did not differentiate trained from untrained HCPs when evaluating SDM support. Although trained observers established a medium effect of the training on SDM support behavior of HCPs, 21 this effect was apparently not sufficiently large to be perceived by APs or it was not meaningful enough to them. In line, we found low correlations between assessments of trained observers and APs.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…This innovative, experimental study demonstrated that cancer patients and survivors (i.e., APs) did not differentiate trained from untrained HCPs when evaluating SDM support. Although trained observers established a medium effect of the training on SDM support behavior of HCPs, 21 this effect was apparently not sufficiently large to be perceived by APs or it was not meaningful enough to them. In line, we found low correlations between assessments of trained observers and APs.…”
Section: Discussionmentioning
confidence: 93%
“…We previously conducted standardized patient assessments (SPAs) before and after a training program on SDM support for GPs and nurses. 21 The video-recorded SPAs were assessed by trained observers to evaluate the trainings’ effectiveness. In the current innovative, experimental study design, video recordings ( n = 32) of SPAs of GPs ( n = 8) and nurses ( n = 8) conducted before (SPA T0) and after (SPA T2) the training were assessed by at least 4 cancer patients or survivors ( n = 132); each participant watched 1 SPA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations